Dynamic performance comparison of DFIG and FCWECS during grid faults - A. M. Shiddiq Yunus; Makmur Saini; Ahmed Abu-Siada (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Among several types, variable speed-based wind turbine generator (WTG) is the most popular type installed worldwide. This type of WTG is able to extract 5% more energy from wind speed compared to the fixed speed WTG. There are two kinds of variable speed based WTG; Doubly Fed Induction Generator (DFIG) and Full Converter Wind Energy Conversion System (FCWECS). DFIG and FCWECS are placed at the first and second topWTG installation worldwide since 2004. However, both of them are very sensitive to the grid dip fault and may violate the allowable margins identified by various international Fault Ride Through (FRT) codes. This paper aims to investigate the responses of DFIG and FCWECS during certain level of grid dips and compare their performanceunder such event. Results show some differences of the performance of DFIG and FCWECS during voltage sag event, however the voltage profile at the point of common coupling is much better in case of DFIG. Results also recommend that DFIG can be effective when connected to weak grids whilst FCWECS is preferably to be connected to strong grids.